Stock assessment and management of cephalopods: advances and challenges for short-lived fishery resources. (3rd May 2020) - Arkhipkin, Alexander I; Hendrickson, Lisa C; Payá, Ignacio; Pierce, Graham J; Roa-Ureta, Ruben H; Robin, Jean-Paul; Winter, Andreas
Abstract: Cephalopods have become an important global food source, but their sustainable management is challenged by unique life history characteristics associated with short lifespans and semelparous reproduction, high natural mortality rates, rapid and often nonasymptotic growth, and complex population structures. Weak stock-recruitment relationships together with the time-consuming work required for age validation and high-volume annual age determinations make traditional age-based modelling impractical. We propose that the best method for cephalopod assessment involves innovative depletion models, fitted with in-season data on catch numbers and fishing effort, to produce realistic estimates of stock biomass. A "fast lane" assessment approach is suggested that includes high-frequency data collection for separate, in-season stock assessments of each cohort to ensure sustainable exploitation of these short-lived resources. However, most cephalopod fisheries are data-poor and/or lack the infrastructure and resources needed to apply depletion methods; therefore, we also present alternative assessment methods that have been recently applied worldwide. We also offer suggestions for further research on the remaining challenges of cephalopod stock assessment and management.